INVENTARISASI NASKAH DAN ANALISIS PENOKOHAN NASKAH HIKAYAT AMIR HAMZAH - Prima Hariyanto (Kantor Bahasa Provinsi Gorontalo, 2020)
Indonesia has many manuscripts that cannot stand the time and are susceptible to temperature changes, making it easy to be damaged or rotten. These are the reasons why it is necessary to arrange an arbitration and research upon these texts. One of the manuscripts that exist in the archipelago treasury is Hikayat Amir Hamzah, which contains a nuanced of the Islamic religion. This manuscript consists of the story of the heroism of Amir Hamzah who often fought to defend Islam. This paper aims to inventory the manuscripts so that the number of these manuscripts is acknowledged, presented the text editing, and the analysis of the characterization of Amir Hamzah. The method used in this research is descriptive method and literature review. The research steps undertaken include data searching, data outsourcing, and data analysis. There are sixteen manuscripts of ofHikayat Amir Hamzah. This does not include the texts that have not been recorded and listed in the catalog. There are many events related to Islamic values in this text, in the form of teaching and example given, such as the advice that reminds us to be sincere, not to betray, arrogant, ripple, and forget the greatness of Allah.